2014
DOI: 10.1007/s11069-014-1473-0
|View full text |Cite
|
Sign up to set email alerts
|

High concentration of acidic species in rainwater at Varanasi in the Indo-Gangetic Plains, India

Abstract: The Indo-Gangetic Plains (IGP), straddling the northeastern parts of India near the foothills of the Himalayas, are one of the most densely populated and polluted regions on the globe, with consequent large anthropogenic emissions. In particular, the use of traditional biofuels in the rural areas along the plains leads to strong emissions of various pollutants. Due to this importance, a comprehensive study on the chemical characteristics of rainwater was carried out during southwest summer monsoon season of 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 58 publications
0
16
1
Order By: Relevance
“…One first reason for this is that Pommier et al (2016) showed a misrepresentation of the fire emissions of HCOOH over India. Secondly, India also encounters excess acidity in rainwater, which could be partly attributed to biomass burning (e.g., Bisht et al, 2014). Concerning Siberia, this region and the surrounding areas experienced intense fires over some years, such as during the summer 2010 (Pommier et al, 2016;, for the region close to Moscow).…”
Section: Modismentioning
confidence: 99%
“…One first reason for this is that Pommier et al (2016) showed a misrepresentation of the fire emissions of HCOOH over India. Secondly, India also encounters excess acidity in rainwater, which could be partly attributed to biomass burning (e.g., Bisht et al, 2014). Concerning Siberia, this region and the surrounding areas experienced intense fires over some years, such as during the summer 2010 (Pommier et al, 2016;, for the region close to Moscow).…”
Section: Modismentioning
confidence: 99%
“…The analytical column IonPac-AS15 with micro-membrane suppressor ASR Sultra II 2 mm, 38 mM Potassium Hydroxide and the IonPac-CS17 column with micro-membrane suppressor CSRS ultra II 2 mm, 6 mM methyl sulfonic acid as eluents and triple distilled water as regenerator were used for anion and cations, respectively. The details of the chemical analysis procedure are discussed elsewhere (Tiwari et al, 2012;Bisht et al, 2015). The data quality was assessed by ionic balance, which is an indicator of the completeness of measured parameters.…”
Section: Chemical Analysis and Quality Controlmentioning
confidence: 99%
“…The scavenging of atmospheric pollutants affects the chemical composition and the pH of rainwater. The acidic rain is primarily caused by incorporation of anthropogenic pollutants such as oxides of sulfur and nitrogen and other acid precursors (Migliavacca et al, 2005;Bisht et al, 2015), whereas, neutralization of acidity in RW can be due to airborne dust and ammonia released from natural and man-made sources (Al-Momani et al, 1995). The amount of the air pollutant reduction by precipitation scavenging effect can be affected by the amount, duration, and intensity of rainfall.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, India also encounters excess of acidity in rainwater, which could be partly attributed to biomass burning (e.g. Bisht et al, 2014).…”
mentioning
confidence: 99%